1992
DOI: 10.1016/0014-5793(92)81281-p
|View full text |Cite
|
Sign up to set email alerts
|

Binding of RNA by the alfalfa mosaic virus movement protein is biphasic

Abstract: The movcmcnt protein of ;rlfal~I mosaic virus wus cxprcsscd in IzrlrrrirlrL ruli tend purified by cation cxchangc chromatography. The purifisd proicin bound singlestranded RPJA caopcntivtly in u biphusic manner. At protein sa~untion. RNAlprotcin cornplcxe (dnigttrtcd 'primnry complexa') wcrc dctatcd by a Ilitroccllulor-ntcntion assay within I min of mixing. bath at 4 and 2X. In contrast, rn incubation of 30 min UI 22.C was nacssary to obtain clectrophorcticolly retarded complcxcs 0ubilizcd camplcxn'), containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Most of the MPs that bind to ssRNA also have ssDNA-binding properties. [22,[34][35][36] Thus, in an attempt to bypass the problems of RNA-protein aggregation and to obtain a more accurate quantitative description of the binding process, [37] we used short ssDNA of different lengths. In this way we avoided the multiple binding of proteins to a single nucleic acid molecule that was probably the cause of the observed complex insolubility.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the MPs that bind to ssRNA also have ssDNA-binding properties. [22,[34][35][36] Thus, in an attempt to bypass the problems of RNA-protein aggregation and to obtain a more accurate quantitative description of the binding process, [37] we used short ssDNA of different lengths. In this way we avoided the multiple binding of proteins to a single nucleic acid molecule that was probably the cause of the observed complex insolubility.…”
Section: Resultsmentioning
confidence: 99%
“…The amount of P3 in transgenic plants was at least equivalent to that found in systemically infected leaves. It was estimated to be around 100 ng/g of fresh material by quantitative Western blot assay (Berna et al, 1986), using Escherichia coli-produced P3 (Schoumacher et al, 1992a) as standard (data not shown). Controls were represented by plants transformed with non-recombinant vectors.…”
mentioning
confidence: 99%
“…1 was obtained by site-directed mutagenesis (creation of unique HindIII sites) and segment reassortment. Mutagenesis was carried out on the plasmid designated pSel 1 .P3N (Schoumacher et al, 1992b Fig. 1.…”
mentioning
confidence: 99%
“…The coding sequences to be expressed, obtained as N c o I -B a m H I fragments from the pSell .P3N-derived plasmids, were inserted between the NcoI and the B a m H I sites of the expression vector pET3d. The recombinant plasmids were cloned into E. coli strain BL21(DE3) and the proteins were extracted from inclusion bodies of the IPTG-induced bacteria with a urea-containing buffer (Schoumacher et al, 1992b). They were purified by SDS-PAGE in a 10 % gel (Laemmli, 1970), eluted from the gel according to Hager & Burgess (1980), renatured by dialysis against 50 mu-Tris-HC1, pH 7.5, containing 10 mM-2-mercaptoethanol and 1% Tween-20 and stored at -2 0 °C after addition of glycerol (50% v/v final concentration).…”
mentioning
confidence: 99%
See 1 more Smart Citation